2019
DOI: 10.4314/evj.v23i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of retrospective rabies suspected cases registered at two hospitals, community and traditional healers’ knowledge, attitude and practices in south Ethiopian pastoralist

Abstract: Despite of available protective rabies vaccines for both human and animal, transmission of rabies from animals to people continues in Africa and Asia. Every year, over 59,000 people are estimated to die from the disease globally. Most of industrialized countries in Europe and North America have eliminated rabies from domestic dog populations. However, in the majority of developing countries, rabies remains endemic in domestic dog and poorly controlled. To understand rabies situation in pastoralist and agro-pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Except for a study by Kabeta et al ( 49 ) that was carried out among dog bite victims attending Jimma Town anti-rabies Health Center located in the Oromia region, the remaining 26 studies were conducted in the community ( 20 , 28–31 , 33–48 , 50–54 ). Twelve of the studies were published in the previous five years (2018–2023 Gregorian Calendar) ( 28 , 30 , 31 , 34–36 , 38 , 40 , 42 , 47 , 48 , 52 ). Eleven of the studies were conducted in the Amhara region ( 20 , 28 , 31 , 35 , 39 , 41 , 44 , 45 , 47 , 51 , 52 ), 9 in the Oromia region ( 29 , 30 , 33 , 38 , 42 , 46 , 49 , 50 ); 3 in Addis Ababa the capital of Ethiopia’s ( 37 , 43 , 53 ); 2 in the Southern Nations, Nationalities, and Peoples’ Region (SNNPR) ( 34 , 54 ), 1 each in Tigray ( 40 ), and Somalia ( 36 ) regions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Except for a study by Kabeta et al ( 49 ) that was carried out among dog bite victims attending Jimma Town anti-rabies Health Center located in the Oromia region, the remaining 26 studies were conducted in the community ( 20 , 28–31 , 33–48 , 50–54 ). Twelve of the studies were published in the previous five years (2018–2023 Gregorian Calendar) ( 28 , 30 , 31 , 34–36 , 38 , 40 , 42 , 47 , 48 , 52 ). Eleven of the studies were conducted in the Amhara region ( 20 , 28 , 31 , 35 , 39 , 41 , 44 , 45 , 47 , 51 , 52 ), 9 in the Oromia region ( 29 , 30 , 33 , 38 , 42 , 46 , 49 , 50 ); 3 in Addis Ababa the capital of Ethiopia’s ( 37 , 43 , 53 ); 2 in the Southern Nations, Nationalities, and Peoples’ Region (SNNPR) ( 34 , 54 ), 1 each in Tigray ( 40 ), and Somalia ( 36 ) regions.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve of the studies were published in the previous five years (2018–2023 Gregorian Calendar) ( 28 , 30 , 31 , 34–36 , 38 , 40 , 42 , 47 , 48 , 52 ). Eleven of the studies were conducted in the Amhara region ( 20 , 28 , 31 , 35 , 39 , 41 , 44 , 45 , 47 , 51 , 52 ), 9 in the Oromia region ( 29 , 30 , 33 , 38 , 42 , 46 , 49 , 50 ); 3 in Addis Ababa the capital of Ethiopia’s ( 37 , 43 , 53 ); 2 in the Southern Nations, Nationalities, and Peoples’ Region (SNNPR) ( 34 , 54 ), 1 each in Tigray ( 40 ), and Somalia ( 36 ) regions. The individual study estimates range from 7.50% ( 39 ) to 99.25% ( 51 ) for a good level of knowledge about rabies, 12.55% ( 53 ) to 95.57% ( 49 ) for a favorable level of attitudes, and 4.69% ( 52 ) to 85.68% ( 28 ) for a good level of practices towards rabies prevention ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 130,673 doses of rabies vaccine were administered to humans and 85,055 doses were administered to animals during this period (Deressa et al, 2010). Moreover, a hospital-based study from the southern Ethiopian pastoral area revealed that 98% of rabies suspected animals bite were due to dog bites (Gum et al, 2019). Dogs are classified as owned, that are restricted within a fenced yard or in the homestead under the owners' supervision, or ownerless/stray dogs that are not under direct human control or not prohibited from freely roaming (Smith et al, 2019).…”
Section: Introductionmentioning
confidence: 99%